2011
DOI: 10.2215/cjn.11291210
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Asymmetric Dimethylarginine for Predicting Death and Cardiovascular Events in ESRD Patients

Abstract: SummaryBackground Endothelial dysfunction as assessed by asymmetric dimethylarginine (ADMA) and inflammation has been consistently linked to atherosclerosis, death, and cardiovascular (CV) events in ESRD patients. Inflammation amplifies the effect of ADMA on the severity of atherosclerosis in ESRD patients, but it is still unknown whether inflammation and ADMA interact in the high risk of death and CV events in this population. Design, setting, participants, & measurementsIn a cohort of 225 hemodialysis patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 40 publications
8
87
0
1
Order By: Relevance
“…In another study, inflammation and endothelial dysfunction as assessed by circulating levels of ADMA were found to be an independent factor for explaining all-cause mortality and cardiovascular events in ESRD patients (18). Similar to this finding, a recent study also reported that ADMA level is a death predictor in ESRD patients (22).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In another study, inflammation and endothelial dysfunction as assessed by circulating levels of ADMA were found to be an independent factor for explaining all-cause mortality and cardiovascular events in ESRD patients (18). Similar to this finding, a recent study also reported that ADMA level is a death predictor in ESRD patients (22).…”
Section: Discussionsupporting
confidence: 56%
“…This finding might suggest that a connection exists between endothelial dysfunction and inflammation in ESRD patients. Recently some studies pointed out the association of ADMA levels with biomarkers of inflammation in some chronic conditions like familial Mediterranean fever, inflammatory bowel disease, and chronic kidney disease (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Those with a CRP > 5 have an increased mortality compared to patients below that threshold [138] and there is a Jshaped association between hsCRP and mortality suggesting that RTRs with very low hsCRP may also be at increased risk of death [139] . More novel markers such as asymmetric dimethylarginine, which is associated with endothelial dysfunction, are also associated with higher risk of mortality (HR = 2.18) and developing CVD (HR = 2.59) in ESRD [140] . Poorer graft outcomes are predicted by IL-6 [136,141] and elevated symmetric dimethylarginine [142] (HR = 5.51).…”
Section: Inflammationmentioning
confidence: 99%
“…The latest study from Tripepi et al [40] showed that inflammation amplified the risk of all-cause mortality and cardiovascular mortality in association with high ADMA levels in this population. However, the prognostic values of ADMA and CRP from this study couldn't be compared with prognostic values from our own study due to the fact that different statistical methods have been applied.…”
Section: Discussionmentioning
confidence: 83%